Physiological and Aberrant γ-Globin Transcription During Development - Barbarani, Gloria; Labedz, Agata; Stucchi, Sarah; Abbiati, Alessia; Ronchi, Antonella E. (Frontiers in Cell and Developmental Biology, 2021)
The expression of the fetal Gγ- and Aγ-globin genes in normal development is confined to the fetal period, where two γ-globin chains assemble with two α-globin chains to form α2γ2 tetramers (HbF). HbF sustains oxygen delivery to tissues until birth, when β-globin replaces γ-globin, leading to the formation of α2β2 tetramers (HbA). However, in different benign and pathological conditions, HbF is expressed in adult cells, as it happens in the Hereditary Persistence of Fetal Hemoglobin, in anemias and in some leukemias. The molecular basis of γ-globin differential expression in the fetus and of its inappropriate activation in adult cells is largely unknown, although in recent years a few transcription factors involved in this process have been identified. The recent discovery that fetal cells can persist to adulthood and contribute to disease raises the possibility that postnatal γ-globin expression could, in some cases, represent the signature of the fetal cellular origin.